PENGARUH PERIKLANAN PRODUK MARASAKE SARI BUBUKKEDELAI INSTAN TERHADAP KEPUTUSAN PEMBELIANWARGA JAMAAH TATANAN WAHYU (JATAYU)PADA UPT. MAKARTI POMOSDA - Nur Hanifah (Reaktom : Rekayasa Keteknikan dan Optimasi, 2018)
In companies large and small, advertising is very important, especially to attract consumers to make purchasing decisions of the company's products and retain the company's customers so that in this case advertising becomes one of the spearhead of marketing for the company. With this researcher want to know how big influence of product advertisement to consumer purchase decision. In conducting this research, researchers used quantitative research methods. The sample used is accidental sampling on the citizens of the Jamaah Revelation Order (JATAYU). The data collection technique is done through the distribution of questionnaires. Testing Likert scale to determine the effect of advertising on consumer purchasing decisions. By using Spearman Rank coefficient obtained rs value of 0.071. This shows that the value of rs has a very weak relationship between variable X (advertising) with variable Y (purchase decision). The magnitude kd of 0.5% of the rest of 99.5% influenced by other variables that are not measured in this study. Based on the calculation of t test analysis with significance level of 5%, obtained t arithmetic of 0.087 and t table of 0.1510. This shows that t arithmetic <t table, so Ho accepted means there is no significant influence between variables X (advertising) with variable Y (purchase decision).